Treatment of Coats' disease with intravitreal bevacizumab. Issue 3 (25th December 2012) - Ray, Robin; Barañano, David E; Hubbard, G Baker
Abstract : Objective: To compare the efficacy of intravitreal bevacizumab plus ablative therapy with ablative therapy alone for Coats' disease. Methods: A retrospective review of all paediatric patients who received treatment for Coats' disease from a single surgeon (GBH) from 1 January 2001 to 31 March 2010 was performed. Ten consecutive patients who received intravitreal bevacizumab as part of their treatment were matched to 10 patients treated with ablative therapy alone by macular appearance, quadrants of subretinal fluid, and quadrants of telangiectasias. Outcomes evaluated were number of treatment sessions, time to full treatment, and resolution of disease. Results: There was no statistical difference between baseline characteristics when comparing the bevacizumab and control groups. Eyes treated with bevacizumab required more treatments over a longer time period compared to the control group. All patients in the bevacizumab group were successfully treated while two of the patients in the control group failed ablative techniques. Conclusions: Intravitreal bevacizumab may play a role as adjuvant therapy in select cases of Coats' disease, but its use does not reduce the time to full treatment. Resolution of disease was seen in the most severe cases treated with bevacizumab plus thermal ablation whereas their matched controls failed therapy with laser and cryotherapy alone.